Pengaruh Penerapan Sistem Informasi Manajemen Karyawan Dan Kepuasan Kerja Terhadap Kinerja Karyawan Plta Kerinci Dengan Disiplin Kerja Sebagai Variabel Intervening - Natasya, Natasya yeli putri; Sari, Marta Widian; Pratiwi, Nila (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This study is targeted to test the impact of implementing employee management information systems & job satisfaction on employee performance with work discipline becoming Intervening using secondary data found by distributing questionnaires to 50 permanent workers used as respondents at the Kerinci Hydropower Plant. This study uses Structural Equation Modeling (SEM) analysis media using Partial Least Square (PLS). The assessment results show that (1) the employee management information system does not have a significant impact (0.674< 0.05) on work discipline. (2) Job satisfaction has a significant & positive impact (0.000 < 0.05) on work discipline. (3) Employee management information system has a significant & positive impact (0.042 > 0.05) on employee performance. (4) Job satisfaction has a significant & positive impact (0.000 < 0.05) on employee performance. (5) work discipline has a significant & positive impact (0.000 < 0.05) on employee performance. (6) Employee management information systems have no significant impact (0.668 < 0.05) on employee performance through work discipline. (7) Job satisfaction has a significant & positive impact (0.000 < 0.05) on employee performance through work discipline.